Impacts of urban safety net on income, food expenditure and intake capacity of poor households in Addis Ababa city, Ethiopia, 2021 - Tareke, Kassa Moges (Frontiers in Sustainable Food Systems, 2022)
Although measures taken to address food insecurity and income inequality showed notable outcomes, they have continued to be major global issues mainly in urban areas of developing countries. To relieve these problems, Ethiopia started an urban safety-net program in Addis Ababa city in 2017. The purpose of this study was to investigate the impacts and progress of urban safety-net mainly cash transfers on income, consumption, and security of food for poor households using indicators based on elements of a theory of change and Engel’s coefficient. It reviewed whether the program is more significant or not to program beneficiaries compared to situations before the start of the program, non-beneficiaries, and beneficiaries’ sex. 560 samples of households were selected through a multi-stage sampling for household surveys. Comparative approaches, Paired & Independent T-tests, and Linear Regression were used to analyze data. Results reveal that the CTs program has satisfactory targeting accuracy of the poor and produced positive effects on monthly income, savings, food expenditures & intake, and seed money for a business start. Since financial transfers account for a larger proportion of the income of households, current income becomes significantly bigger compared to income of pre-program period and non-beneficiary households. Food access, expenditure, and savings capacities of beneficiaries in post-financial transfer became better than in pre-cash transfers as well as better food access and diet intake 2-3 times a day than non-beneficiaries. Besides, coverage and benefits are statistically significant for women compared to men's households. Urban safety-net implementation is good in its positive impacts and progress towards food security of poor households as a result of enhancement in income, food expenditure, intake, and access. This implies policymakers could potentially expect to see improvements in food security, especially when targeting urban poor and female-headed households. However, delays in payments and work equipment, declining size & value of payments, and weak supplementary services are program shortcomings. Policy implications to improve the size of transfers, emergency aids, timely payments & equipment provisions, and interventions like regular business training, supervision, and guidance were recommended.